Preferences of public sector medical doctors, professional nurses and rehabilitation therapists for multiple job holding regulation: A discrete choice experiment - Busisiwe Precious Matiwane; Laetitia C. Rispel; Duane Blaauw (PLoS ONE, 2025)
Introduction Regulating multiple job holding (MJH) among health professionals is challenging for many health systems. The effectiveness of different MJH policy reforms depends on the behavioural responses of different groups of health professionals but little is known about their preferences and likely reactions. Aim Investigate the preferences of public sector medical doctors, professional nurses, and rehabilitation therapists for different MJH regulations in two South African provinces. Materials and methods We developed a novel discrete choice experiment (DCE) to evaluate the preferences of health professionals for jobs with varying MJH policy interventions. The DCE attributes included restrictive regulations (banning MJH) versus reward-oriented policies (increased public sector salaries, expanded overtime, improved clinical practice environment, and better hospital management). We produced an unlabelled DCE using an efficient design and administered it to a representative sample of health professionals. Generalized multinomial logit models were used for analysis. We also investigated group heterogeneity, calculated marginal willingness to pay and estimated uptake for different policies. Results 1387 participants completed the DCE. The doctors, nurses and rehabilitation therapists were strongly opposed to banning MJH, requiring salary increases of 45.7%, 20.0% and 42.8%, respectively, to accept an MJH ban. Increased public sector salaries significantly increased public sector retention. However, non-financial interventions were also influential. Doctors, nurses, and rehabilitation therapists were willing to forgo 57.9%, 54.8%, and 38.9% of their salaries, respectively, for an improved clinical practice environment. Competent hospital management was also important. There was some preference heterogeneity. Nurses had significantly different preferences for certain attributes compared to the other two groups, and professionals currently engaged in MJH were significantly more opposed to banning MJH. Conclusion This study provides new information on health professional preferences for different MJH regulations. It confirms the importance of non-financial policy interventions in addressing MJH and the need to tailor MJH policy design.